2014
DOI: 10.1080/17550874.2013.879942
|View full text |Cite
|
Sign up to set email alerts
|

Soil-induced impacts on forest structure drive coarse woody debris stocks across central Amazonia

Abstract: Background: Coarse woody debris (CWD) is an essential component in tropical forest ecosystems and its quantity varies widely with forest types.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 46 publications
(72 reference statements)
2
25
0
Order By: Relevance
“…Mean annual precipitation in this area varies from 2,100 to 2,700 mm (Hijmans, Cameron, Parra, Jones, & Jarvis, 2005), with on average two to three consecutive months with <100 mm rainfall (dry months) per year (Sombroek, 2001). Soils are predominantly Plinthosols and Gleysols, the predominant texture is silt to fine sand, with poor drainage, and varying degrees of soil water saturation and anoxic conditions (Martins et al, 2014;Sombroek, 2000). Soils physical structure is generally dense and restrictive to root growth, with varying degrees of hardness and effective soil depth (Quesada et al, 2010).…”
Section: Study Area and Sampling Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Mean annual precipitation in this area varies from 2,100 to 2,700 mm (Hijmans, Cameron, Parra, Jones, & Jarvis, 2005), with on average two to three consecutive months with <100 mm rainfall (dry months) per year (Sombroek, 2001). Soils are predominantly Plinthosols and Gleysols, the predominant texture is silt to fine sand, with poor drainage, and varying degrees of soil water saturation and anoxic conditions (Martins et al, 2014;Sombroek, 2000). Soils physical structure is generally dense and restrictive to root growth, with varying degrees of hardness and effective soil depth (Quesada et al, 2010).…”
Section: Study Area and Sampling Designmentioning
confidence: 99%
“…Higher scores denote more limited soil conditions for plant roots. Soil physical classification was determined in 2 m deep pits dug in each research site and in soil-profile samples from all plots (Martins et al, 2014). As a proxy of soil fertility we used the available phosphorus content (extracted with Mehlich-1; EMBRAPA, 2011) determined from a compound sample derived from six subsamples from the first 30 cm soil depth (Schietti et al, 2016).…”
Section: Environmental Datamentioning
confidence: 99%
“…Two classes of models have been used for CDW estimation using lidar: (1) area-based models estimate CDW indirectly based on lidar metrics calibrated with data from forest inventory plots (Martinuzzi et al, 2009;Pesonen et al, 2008), and (2) individual-based models identify standing dead trees . Wall-to-wall maps and histograms of total CDW predicted by lidar-only models at landscape level (166 m resolution).…”
Section: Comparisons To Other Lidar-related Modelsmentioning
confidence: 99%
“…At this scale, there is a significant positive relationship between aboveground live biomass and necromass stock (Chao et al 2009). However, an extensive survey of necromass on a northsouth transect from the Manaus area to Humaitá found no relation to aboveground live biomass, differences in necromass stocks being explained instead by soil quality and other limitations on site quality for tree growth (Martins et al 2014). In a pantropical review, Palace et al (2012) found that undisturbed forests had a peak of b Fig.…”
Section: Necromass (Dead Biomass)mentioning
confidence: 99%